Contribuição do estágio supervisionado para a formação do enfermeiro na perspectiva do discente - Bezerra, Rutheale Alves (2018)
The aim of this academic work of conclusion of course is the Supervised Curricular Internship for the training of nurses, consisting of a scientific article entitled "Contribution of the supervised internship to the training of nurses: the perspective of the student" and two intervention products: the Technical Report and the Virtual Communication Channel. This study is part of the line of research, curriculum and teaching-learning process in health. In the Supervised Curricular Internship, the student has the possibility of experiencing learning experiences directly related to the daily life of individuals and communities that demand answers very close to what is expected of him as a health professional. In this context, the objective of this study is to analyze the contribution of the supervised curricular internship to the training of the nurse professional. It is a descriptive and qualitative approach, carried out in a private institution in the interior of Pernambuco. Fifteen nursing students from the last semester participated in the study. The data were obtained through a semi-structured interview, guided by a form developed for the research. For the analysis was used the Content Analysis, in the thematic modality. The results demonstrated that the supervised curricular stage: allowed re-signification of the learning, considering professional, relational and effective learning; the role of the nurse; favored the recognition of the role of the preceptor as facilitator in the teaching-learning process; provided technical skill and safety related to care practice. The results also revealed that the managerial practice was little lived and the educational practice was more related to continuing education and health education than to permanent education. Critical thinking was referenced in the sense of a self-evaluation of the performance of other professionals, to the detriment of the perspective of the transforming praxis. It is believed that the results of this research are important to favor the critical reflection on the supervised curricular internship, with the intention of improving it and ensuring that it is a potentiator of the training of nurses focused on caring for people and communities, attending to their needs and the transformation of reality and work environments. From these results, two products were elaborated that intend to be na important contribution to the institution where the study was carried out. The first is a report with the main results of the research to be delivered to the Coordination of the Course and to the Internship. The second is an instrument that will contribute to the evaluation of the stage, to be answered by the students in a virtual communication channel. Such na instrument Will allow knowing the student's perspective on the internship, as well as, it represents the recognition of its protagonist in the teaching-learning process.